10-Year Trends in Epidemiology, Diagnosis, and Treatment of Cutaneous Leishmaniasis in Hamadan Province, West of Iran (2007–2016) - Akhlagh, Azita; Salehzadeh, Aref; Zahirnia, Amir Hossein; Davari, Behrooz (Frontiers in Public Health, 2019)
Background: Cutaneous leishmaniasis is one of the most important infectious diseases in the world. The aim of this study was to determine the epidemiological pattern of cutaneous leishmaniasis in a 10-year period in Hamadan Province. This study was considered necessary due to the lack of new information in recent years on the epidemiology of disease. Methods: This is a descriptive study. The data of patients who were diagnosed with cutaneous leishmaniasis in Hamadan health centers were collected during 10 years (2007-2016) and were analyzed using SPSS software. Results: Of the 908 registered patients, 94% were male and 4% were female. The mean age was 32.7 ± 11.8%. About 87.1% of patients had a history of travel to endemic areas. The highest incidence rate was observed in year 2015 with a rate of 12.6 and the lowest was in 2008 at 1.5 per 100,000 people. 21 out of 61 cases in Bahar city of Hamadan Province did not mention travel history in 2015. Conclusion: Due to increasing trend in number of cutaneous leishmaniasis in Hamadan and effect of occupation, high risk groups such as drivers should be informed of preventive measures like using insect repellents. Also Considering the possibility of shaping a new hotspot in the province, a throughout reviews and more comprehensive entomological studies is recommended.